The bully-proof workplace : essential strategies, tips, and scripts for dealing with the office sociopath - Dean, Peter J., 1946-; Shepard, Molly Dickinson (McGraw Hill-Ascent Audio, 2017)
Smart strategies for managing workplace bullies out of your life and business More than one in four Americans deals with an on-the-job bully. These office sociopaths don't just make individuals miserable. Their poison spreads throughout the company, damaging overall morale, creativity, productivity, and profitability. It doesn't have to be this way. Leading consultants Peter Dean and Molly Shepard have helped vanquish workplace bullying and now share their proven methods with you. In The Bully-Proof Workplace, they provide vital insight into the four major types of bullies: The Belier Weapons of choice: slander, deception, and gossip The Blocker Weapons of choice: negativity and inflexibility The Braggart Weapons of choice: narcissism and a sense of superiority The Brute Weapons of choice: aggression and intimidation These bullies may operate differently, but they all have one thing in common: a desperate need for control based on deep-seated fear and insecurity. This invaluable survival guide equips individuals with strategies, tips, and scripts for managing interactions with bullies. Managers learn how to identify bullying, deal with it swiftly, and introduce zero tolerance for such behavior. And executives gain the information they need to create a corporate policy regarding bullying. We spend about 60 percent of our waking moments at work. Spending that much time under the thumb of a bully and dealing with the negative business effects of bad behavior is simply unacceptable. Whether you're a victim of bullying or a business leader tasked with building a collaborative corporate culture, The Bully-Free Workplace provides the critical insight and practical tools you need to successfully combat this ubiquitous but rarely addressed business challenge and ensure that bullies behave-or leave-so you and everyone else can get on with your work.